Pengaruh Risk Profile, Good Corporate Governance, Earning, Capital terhadap Value of Firm di Bursa Efek Indonesia - Rhevinalda Bima Prakarsa; Winwin Yadiati; N. R. Handiani Suciati (Universitas Proklamasi 45 Yogyakarta, 2020)
The purpose of the company is to increase firm value. But in the last six years, the firm value of the banking sector has fluctuated and even tends to decrease. The level of banking health can be expected to increase firm value. The level of banking health can be measured using the Risk Profile (RP), Good Corporate Governance (GCG), Earning, Capital (RGEC) method which is the latest formula after Capital, Asset Quality, Management, Earning, Liquidity (CAMEL). The purpose of this study was to determine the effect of banking health on the firm value. The research method uses partial panel data regression through the determination of the estimation model and the classical assumption test in advance using 33 banks listed on the Indonesia Stock Exchange (IDX). The results showed that there was a significant and positive effect between Return on Asset (ROA) and Capital Adequacy Ratio (CAR) on firm value. Besides, there was a positive but not significant effect between GCG and risk profile on firm value. The results showed that capital is a factor of business developer and company earning can show as a signal of quality prospects. The application of GCG is not a significant influence because the results of self-assessment are not following fraud that occurs. Banks must be able to manage their risk so that the risk can be an encouragement for them to produce high values.